Comparative Study of Burden of Proof in Civil Procedure and Consumer Protection Law - Almira Balqis; Sulistianingsih , Dewi; Pujiono , Pujiono (Universitas Negeri Semarang, 2025)
This article compares the burden of proof system in resolving consumer disputes under Indonesian Civil Procedure Law and the Consumer Protection Law. It addresses two primary issues: the divergence in evidentiary burdens and the dispute resolution mechanisms adopted by each legal regime. Employing a normative-juridical research method, this study analyzes both primary and secondary legal materials using legislative and comparative legal approaches. The findings reveal that Civil Procedure Law adopts the principle of actori incumbit probatio, where the burden of proof lies with the plaintiff—often disadvantaging consumers due to their limited access to evidence and legal resources. In contrast, the Consumer Protection Law (Law No. 8 of 1999) introduces a reverse burden of proof, requiring business actors to prove they are not at fault, thereby offering more equitable legal protection. The article includes case studies such as Supreme Court Decisions No. 681/Pdt.G/2019/PN.Jkt.Sel. and No. 175 K/Pdt.Sus-BPSK/2021 to illustrate the practical consequences of each burden of proof model. The analysis underscores the structural disadvantage consumers face under traditional civil litigation and how the reverse burden compensates for this imbalance. This research contributes to legal scholarship by clarifying legal terms (burden of proof, presumption, and standard of proof) and by emphasizing the need for procedural harmonization. Additionally, it contributes to the development of consumer law in Indonesia by offering doctrinal clarification and practical recommendations to strengthen access to justice. Ultimately, the study recommends aligning evidentiary standards with substantive justice to enhance consumer protection and ensure fairness in dispute resolution systems.